An Endoplasmic Reticulum CREC Family Protein Regulates the Egress Proteolytic Cascade in Malaria Parasites - Fierro, Manuel A. (mBio, 2020)
The endoplasmic reticulum (ER) is thought to play an essential role during egress of malaria parasites because the ER is assumed to be required for biogenesis and secretion of egress-related organelles. However, no proteins localized to the parasite ER have been shown to play a role in egress of malaria parasites. In this study, we generated conditional mutants of the Plasmodium falciparum endoplasmic reticulum-resident calcium-binding protein (PfERC), a member of the CREC family. Knockdown of the PfERC gene showed that this gene is essential for asexual growth of P. falciparum. Analysis of the intraerythrocytic life cycle revealed that PfERC is essential for parasite egress but is not required for protein trafficking or calcium storage. We found that PfERC knockdown prevents the rupture of the parasitophorous vacuole membrane. This is because PfERC knockdown inhibited the proteolytic maturation of the subtilisin-like serine protease SUB1. Using double mutant parasites, we showed that PfERC is required for the proteolytic maturation of the essential aspartic protease plasmepsin X, which is required for SUB1 cleavage. Further, we showed that processing of substrates downstream of the proteolytic cascade is inhibited by PfERC knockdown. Thus, these data establish that the ER-resident CREC family protein PfERC is a key early regulator of the egress proteolytic cascade of malaria parasites.